ANALISIS SISTEM DAN PROSEDUR PENYUSUNAN LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAHAN PADA DINAS PARIWISATA KOTA MANADO - Assa, Yuuki Jonas John; Sabijono, Harijanto; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
In order to encourage the creation of performance accountability, government agencies need an accountability system so that they can operate efficiently and effectively to realize the transparency of government agencies and maintain public trust in the government, especially the City Government of Manado. This study aims to investigate and describe the System Manado City Government Especially at the Tourism Office. The research method used is descriptive analysis method. The results of this study indicate that the Implementation of the Performance Accountability System of the Manado City Government Agency can improve better transparency where this system is an integration of the planning system, budgeting system, and performance reporting system that is in line with the implementation of the financial accountability system. In this case, each agency, both the leader and the work device, is obliged to record and report on the use of state finances and their suitability with the applicable rules, but in the implementation there are still several obstacles, namely Human Resources that are less understanding and lacking in coordination between providers and trustee / budget users in the institution so that there are differences in the report documents obtained.